Pengaruh Daya Serap Siswa terhadap Mata Pelajaran Kejuruan Kelas X Jurusan Manajemen Perkantoran SMK PGRI 1 Pasuruan - Leli Amalia Putri; Sugeng Pradikto (Institut Nalanda, 2025)
The purpose of this study is to examine how absorption affects vocational topics for class X Office Management majors at SMK PGRI 1 Pasuruan. Ten respondents in grade X were given questionnaires as part of the quantitative methodology used to collect data. Descriptive statistics were used in the data analysis process to gauge the degree of student absorption. The findings demonstrated a strong correlation between learning outcomes in vocational topics and absorption. According to the findings, 75% of respondents had a good degree of absorption, as evidenced by their comprehension of the subject matter and their capacity to apply the ideas they had learned. Learning strategies, the learning environment, and student motivation are a few of the elements that affect absorption. These results suggest that studying vocational topics successfully depends on absorption. In order to boost students' retention of vocational courses, this study suggests that learning strategies be optimized and a supportive learning environment be established.